Efektifitas Metode Tartili dalam Pembelajaran Al-Qur'an bagi Anak Usia Dini: Pendidikan Al-Qur'an - Zulkifli (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2023)
Al-Quran learning using the Tartili method is very easy and practical to apply to young children. At an early age is the golden age or golden period where children will be responsive and can quickly read the Quran properly and correctly. This paper aims to describe the effectiveness of the Tartili method in learning to read the Quran for Early Childhood, which is examined through several literatures related to the subject, using qualitative descriptive analysis. In conclusion, the Tartili method is very suitable and very effective to improve learning to read the Quran for early childhood because the process is very easy, on the other hand children at an early age are at the golden age or golden stage of development where children will respond quickly to what their teachers teach. Children can easily read hijaiyah letters perfectly and correctly.